A dual feed PIN diode based switchable multiband planar meandered antenna for intelligent transportation system application. Issue 11 (20th August 2019) - Tripathi, Shivesh; Pathak, Nagendra P.; Parida, Manoranjan
Abstract: This article presents a dual feed switchable coplanar linearly polarized multiband meandered microstrip patch antenna. The antenna provides multiband functionalities with switching allowable at one of the nine adjacent frequencies. The proposed antenna, loaded with two symmetric PIN diodes, comprises dual‐patch configuration and excited by coplanar microstrip feeds, it operates within 1 to 15 GHz frequency bands. The induced current of the antenna can be changed by switching the diodes, resulting in different operating frequency bands. The antenna has a nearly broadside radiation pattern and the impedance bandwidth is obtained up to 47% having a center frequency of 2.4 GHz for band range of 1 to 15 GHz. The measured gain of the antenna for 1.57, 2.4, 4.5, 4.71, 5.9, 6.53, 7.59, 10.8, and 11.87 GHz are 5, 5, 7, 6, 6.1, 4.4, 3.8, 3.5, and 1.87 dBi, respectively. The antenna has advantages of the simple biasing network, easy fabrication, and adjustment. It is suitable for many modern wireless communication systems like intelligent transportation system. This antenna is also useful in direct broadcast satellite applications.